Pemikiran dan Inovasi Pendidikan Islam Menurut Al-Qabisi: (Studi kasus di SDIT Addzimat DAI Indonesia Bandung) - Nanang Kosim Rohmana; Suhud; Iyad Suryadi; Helmawati (Indonesian Journal of Islamic Education Studies (INJURIES), 2024)
This study aims to make relevant the ideas of Al-Qabisi's thoughts about his concern for children's education, especially at SDIT Ad-Dzimat DAI Indonesia Rancaekek Bandung, West Java. Al-Qabisi himself is one of the classical Muslim figures who has a great influence on changes in education and learning, especially in the field of Islam. In particular, Al-Qabisi discusses education and learning for children, with an orientation towards educational institutions. His thoughts or views are more directed towards the concept of children's education, educational information, objectives, assessment practices, praise, fines, methods, learning models and teaching techniques as well as discussions about philosophy in Islamic education. This study is a qualitative study. Data collection was carried out using in-depth research methods, documentation, namely through scientific writing such as books, journals, encyclopedias and others which are used as document analysis to help complete the results of the study. While the results of this study found two parts of the curriculum brought by al-Qabisi, namely the ijbari curriculum and the ikhtiyari curriculum. Religious education and noble morals are very important to ensure prosperity in society and the country. Keywords: Al-Qabisi; Educational Thought; Islamic Education